5-Azacytidine incorporated polycaprolactone-gelatin nanoscaffold as a potential material for cardiomyocyte differentiation. Issue 1 (2nd January 2020) - Rachel, Kerena; Pathak, Surajit; Moorthi, A.; Narasimhan, Srinivasan; Murugesan, Ramachandran; Narayan, Shoba
Abstract: India has an alarming rate of growth of cardiovascular diseases (CVD). Similar to cancer there is a significant role for epigenetic factors in the increasing prevalence of CVD. Targeting the epigenetic mechanism, viz., the DNA methylation processes, histone modifications, and RNA based arrangements is today considered as a potential therapeutic approach to CVD management. 5-Azacytidine is an epigenetic treatment drug that is involved in the demethylation of DNA. 5-Azacytidine is an FDA approved drug for myelodysplastic syndrome. However, the usage of 5-Azacytidine for CVD has not been found acceptable because of its poor stability in neutral solutions and shorter half-live which makes it toxic to the cells. A significant breakthrough in the use of 5-azacytidine for cell therapy and tissue engineering for CVD treatment has been gained based on its ability to differentiate mesenchymal stem cells into cardiomyocytes. This work addresses the further need for a sustained release of this drug, to reduce its toxicity to the stem cells. Electrospun PCL-gelatin fibres that are well aligned to provide a mat-like structure with sufficient porosity for differentiated cells to move forward have been synthesized. The crystalline character, porosity, fibre width, thermal behavior hydrophilicity of these scaffolds are in tune with those reported in the literature as ideal for cell proliferation and adhesion. FTIR measurements confirm the entrapment of 5-azacytidine on to the scaffold. The adsorption of the drug did not alter the characteristic features of the scaffold. Primary results on cell viability and cell morphology, as well as cardiomyocyte differentiation, have shown that PCL-gelatin scaffolds carrying 5-azacytidine developed in this work could serve as an ideal platform for mesenchymal stem cell differentiation into cardiomyocytes.